PERANCANGAN KORIDOR JALAN DIPONEGORO PONTIANAK, KALIMANTAN BARAT - Ikhtiari, Anang Ridha; Aufa, Naimatul (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
Diponegoro Street is a festival road and has a corridor, the corridor has no space to support festival activities or other social activities. The design of the Diponegoro Street Corridor is a public space, has a function as social space, and Pontianak cultural space (Malay, Dayak, and Chinese). The goal is achieved by applying the concept of "The Canopy City" a corridor that accommodates a variety of functions (Cultural Room, Festival Room, Street Room, Social Space and Economic Space), and utilizing the activities of the surrounding shop houses to support activities.